Microstructure and mechanical properties of SiCp/AZ91 composites processed by a combined processing method of equal channel angular pressing and rolling - Qiong Xu (Elsevier, 2021)
In this study, SiCp/AZ91 composites with enhanced mechanical properties was successfully obtained by a combined process route of equal channel angular pressing (ECAP) and rolling. The effect of ECAP and rolling on the microstructure and mechanical properties of SiCp/AZ91 composites were investigated by comparative analysis. Results showed that the high-pass ECAP process effectively refined the matrix grains and dispersed the SiCp, which gave rise to the final formation of homogenous microstructure in the rolled plate. A non-basal texture with high Schmidt factors was formed by ECAP process, while after rolling it turned into basal texture with relatively lower Schmidt factors. The SiCp/AZ91 composite obtained by the combined process method exhibited superior mechanical properties (yield strength of ∼348 MPa, ultimate strength of ∼411 MPa) and improved ductility (elongation of ∼6.3%) than the composite singly processed by rolling. The enhanced mechanical properties should be contributed to the homogenized microstructure with refined grains, uniformly distributed SiCp, accumulated dislocations and transferred texture.